The Analysis of Satisfaction Level from Renewable Energy Sources Usage Co-Financed from European Funds in the Rossosz Commune - Sałuch Mateusz; Siłuch Marta; Tokarski Daniel; Żukiewicz-Sobczak Wioletta; Sobczak Paweł (Studia Ekonomiczne i Regionalne, 2018)
Subject and purpose of work: the purpose of this article is to present the opportunities for rural development and the benefits of participation in the Regional Operational Program of the Lublin Province for the years 2007-2013, as well as the estimation of the level of satisfaction of the inhabitants of the Rossosz Commune in the Bialski Poviat, Lublin Province, using renewable energy sources co-financed by EU funds. Materials and methods: this work was created with the use of author’s interview questionnaire as the basic research tool. The survey was carried out among the inhabitants of the Rossosz Commune. Results and conclusions: participation in the “Clean Energy in the Zielawy Valley” project contributed to the development of rural areas in the Biała Podlaska Poviat of the Lubelskie Province and it was a fundamental factor enabling the installation of devices using renewable energy. The research shows that the vast majority of respondents appreciated the benefits of renewable energy installations and many of them envisage to make use of the possibility of installing renewable energy devices in the near future.